Ankle “sprains” during sport activities with normal radiographs - Yammine, Kaissar (2011)
Objectives To evaluate, with magnetic resonance imaging (MRI), the occurrence of bone and tendon injuries and their impact on clinical management in athletes with ankle trauma during sports activities having normal radiographs and referred to the orthopedic department as “ankle sprains”. Methods This was a prospective study of 54 patients. Clinical examination and MR imaging were done in order to have an accurate diagnosis and the incidence of those injuries. Results Nearly half of the patients were found to have no ligament injury on MRI. Isolated bone bruises and isolated tendon injuries may share the same clinical signs with ankle sprains. Conclusions MRI-based clinical management has been adjusted for each case; beside the Grade 3 ligament injuries and the rare, but difficult to diagnose osteochondral lesions of the talus, partial weight bearing or short-immobilization were offered as treatment modalities for the rest of the patients avoiding unnecessary long-term treatments and rehabilitation exercises.